La coexistencia entre el mythos y el logos en la dialéctica de la ilustración de Horkheimer y adorno - Mantuano Macías, Diego Omar (2022)
The present research studies the dialectic between myth and reason based on Horkheimer and Adorno's Dialectic of Enlightenment. The context of this work is the twentieth century and the Second World War. Here, an enlightened reason emerges dominated by its own contradictions: the destruction of human life. Myth is what precedes reason and reason precedes myth. Therefore, it is a matter of understanding myth in relation to reason, for this we turn to Homer's epic: Odyssey. Odysseus is identified as a rational being who separates himself from the myth and in doing so loses his identity. Therefore, Odysseus exemplifies the modern subject. On the other hand, that understanding of the myth leads to a reflection on reason and its relationship with the culture industry. The concept of cultural industry appears. This concept is extracted from Dialectics of the Enlightenment to evidence the negation of reason and the submission of the modern subject. Finally, a synthesis of this dialectical process is proposed, where myth and reason coexist transforming the human being in his relationship with himself and with the world.